PENGGUNAAN DAUN KEMANGI (Ocimum basilicum) DAN GARAM DAPUR (NaCl) SEBAGAI BAHAN PENGAWET PADA IKAN SELAR (Selaroides spp) KUKUS - Aristawati, Anita Treisya (JSTT, 2016)
Basil leaves and salt is a seasoning and spice native to Indonesia which has antibacterial compound. This study aims to determine the effect of the use of salt and basil leaves on the organoleptic quality, moisture content, pH and total number of microbes on the steamed fish. . The method used in this study is the experimental method by combining the concentration of salt and basil leaves. The treatment is done is G1K1 (1.5% saline + 2% basil), G1K2 (1.5 salt% + 4% basil), G1K3 (1.5% salt + 6% basil), G2K1 (3% salt + 2% basil ), G2K2 (3% salt + 4% basil), G2K3 (3% salt + 6% basil), G3K1 (4.5% saline + 2% basil), G3K2 (4.5% saline + 4% basil), G3K3 (4.5% salt + 6% basil). Analysis of data using completely randomized factorial design to test the pH and water content, and a randomized complete block design for organoleptic test. Research shows the effect of the use of natural preservatives basil leaves and salt to the organoleptic quality (texture and mucus), moisture content, pH and steamed fish are stored for several days at room temperature. Degradation of the organoleptic, microbiological quality, moisture content, and pH occurs with increasing steamed fish steamed fish shelf life. This is because the activities of microorganisms on foodstuffs is increasing due to long storage. In general, for treatment organoleptic testing is best seen in treatment G1K1 (1.5% salt + basil leaves 2%).